Identification of duplicate accessions in the pea (Pisum sativum L.) collection at VIR - E. V. Semenova; V. V. Vasipov; I. N. Anisimova (Труды по прикладной ботанике, генетике и селекции, 2022)
Background. Identification of duplicates in the collections of genetic resources is the most important problem of seed gene bank management. Duplicate accessions expand the collection size, thus raising the costs of germplasm maintenance without broadening the genetic diversity.Materials and methods. The studied material included 17 pairs of Pisum sativum L. accessions from the VIR collection which presumably had been erroneously registered twice in the VIR catalogue; however, they had identical introductory numbers. The accessions entered the collection in 1922–1996 and to date they have been reproduced 2 to 16 times. After a field assessment, 15 pairs of putative duplicate accessions of various uses were selected for molecular analysis. A RAPD analysis was performed using five primers from the Operon Series. Total seed proteins were analyzed by SDS-polyacrylamide gel electrophoresis.Results. The following criteria were used to ascertain identity of the accessions or their difference: 1) similarity of morphological characters (habitus, and anthocyanin pigmentation of flowers and vegetative organs) and flowering dates; 2) identity or polymorphism of RAPD profiles; and 3) identity or difference in electrophoretic banding patterns of seed storage proteins. Seven pairs of duplicates were identified according to the results of a comparative analysis. Among them, the accessions in the pairs k-81/k-1199, k-8331/k-8645, k-8719/k-8760, and k-8757/k-8825 turned out to be completely identical, while k8464/k-8472, k-8740/k-8873, and k-8689/k-8723 were heterogenic, but had similar RAPD profiles and seed proteins patterns.Conclusions. An integrated assessment involving in-field plant phenotyping and analyzing polymorphism of amplified DNA fragments and components in electrophoretic banding patterns of seed proteins is promising for detecting identical or heterogenic accessions in genebank collections.